B-Vitamin Sharing Promotes Stability of Gut Microbial Communities - Sharma, Vandana; Rodionov, Dmitry A.; Leyn, Semen A.; Tran, David; Iablokov, Stanislav N.; Ding, Hua; Peterson, Daniel A.; Osterman, Andrei L.; Peterson, Scott N. (Frontiers in Microbiology, 2019)
Cross-feeding on intermediary and end-point metabolites plays an important role in the dynamic interactions of host-associated microbial communities. While gut microbiota possess inherent resilience to perturbation, variations in the intake of certain nutrients may lead to changes in the community composition with potential consequences on host physiology. Syntrophic relationships and mutualism at the level of major carbon and energy sources have been documented, however relatively little is known about metabolic interactions involving micronutrients, such as B-vitamins, biosynthetic precursors of essential cofactors in the mammalian host and numerous members of the gut microbiota alike. In silico genomic reconstruction and prediction of community-wide metabolic phenotypes for eight major B-vitamins (B1, B2, B3, B5, B6, B7, B9 and B12), suggests that a significant fraction of microbial gut communities (>20% by abundance) are represented by auxotrophic species whose viability is strictly dependent on acquiring one or more B vitamins from diet and/or prototrophic microbes via committed salvage pathways. Here we report the stability of gut microbiota using humanized gnotobiotic mice and in vitro anaerobic fecal culture in the context of extreme variations of dietary B vitamin supply as revealed by phylotype-to-phenotype prediction from 16S rRNA profiling and metabolomic measurements. The observed nearly unaltered relative abundance of auxotrophic species in gut communities in the face of diet or media lacking B vitamins or containing them in great excess ( 30-fold above normal) points to a strong contribution of metabolic cooperation (B vitamin exchange and sharing) to the stability of gut bacterial populations.